Experimental investigation into metal micro-patterning by laser on polymer-metal hybrid joining. (August 2018) - Rodríguez-Vidal, E.; Sanz, C.; Lambarri, J.; Quintana, I.
Highlights: The structuring is conducted by pulsed and continuous wave laser radiation. The complete joining process can be carried out by the same laser source. The dependence of pattern geometry on the joint's mechanical response is proved. There is not effect of clamping pressure values on the joint's mechanical behavior. Abstract: Surface modification pretreatment on laser direct joining of glass fibre reinforced polyamide to steel was studied to assess its effect on the joint's mechanical performance. The steel part was structured by laser radiation to accomplish a proper mechanical interlock when joining with the polymer. In a second step, the opposite side of the micro-structured metal was irradiated by a continuous wave (cw) fibre laser system until reaching the melting temperature of the polymer in both materials interface. The metal micro-structuring was produced by two different laser sources (nanosecond pulses (ns) and cw) in order to study the effect of different groove geometries on the joint's failure force under tensile-shear tests. The impact of structure density and clamping pressure was also assessed. A tight dependence of aspect ratio and recast material height of patterns on joint's failure force was found for the micro-patterns that were produced by nanosecond pulses. The greatest strength was achieved in the case of patterns produced by ns-pulses. The trend concerning the effect of structure density was validated for the patterns that were produced by ns-pulses and cw-radiation. The changes in clamping pressure did not evidence a significant influence on the joint quality. The morphological features of the detached surfaces showed that the micro-geometric structure aspect ratio has a meaningful effect on the failure mode in the case of structures that were generated by nanosecond pulses.